African Legislators: Unrepresentative Power Elites? - Mattes, Robert; Krönke, Matthias; Mozaffar, Shaheen (Journal of Southern African Studies, 2024)
African legislators both resemble and differ from the societies they claim to represent in important ways. Based on a unique survey of representative samples of parliamentarians in 17 countries, we find that legislatures are representative of national publics in terms of ethnicity and religion. At the same time, compared to ordinary African citizens, African MPs possess far higher levels of education and are far more likely to be older, male and to come from professional or business backgrounds. Besides coming from higher social and economic status backgrounds, many MPs also previously held senior posts in the state and national government, or leadership positions in their political party. Does this mean that African legislators constitute a coherent, self-interested, social, economic and political 'power elite' detached from the interests of the voters? In the legislatures under investigation, we find little evidence of this effect. Markers of social, economic or political privilege and power overlap irregularly and in a non-cumulative way. For example, while MPs are significantly older than the average voter, we find that most African legislators are in their first term of office. Thus, far from comprising a slowly changing, cohesive and self-interested elite, characterised by overlapping and cumulative markers of social and political influence, Africa's legislators come from a plurality of social and political backgrounds, and are relative legislative neophytes.